Exploring social media appearance preoccupation in relation to self-esteem, well-being, and mental health - Rosa Angela Fabio; Rosa Tripodi (Health Psychology Report, 2024)
Background Social media platforms have become integral to modern society, facilitating diverse content interactions for individuals. The widespread use of social media has sparked intriguing inquiries into its impact on self-perception and individual well-being. This study investigated the phenomenon of social media appearance preoccupation and its complex relationship with psychosocial factors such as self-esteem, well-being, appearance-related anxiety, depression, and anxiety, considering both the rich-get-richer hypothesis and the poor-get-richer hypothesis.